Gut microbiota-mediated metabolic restructuring aggravates emotional deficits after anesthesia/surgery in rats with preoperative stress - Lei, Lei; Ji, Muhuo; Yang, Jinjin; Chen, Sai; Gu, Hanwen; Yang, Jian-jun (Frontiers in Immunology, 2022)
Patients with preoperative stress are prone to postoperative emotional deficits. However, the underlying mechanisms are largely unknown. Here, we characterize the changes of microbial composition and specific metabolites after anesthesia/surgery in rats with preoperative stress based on 16S rRNA gene sequencing and non-targeted metabolomics technique. Consequently, we found that anesthesia/surgery aggravated anxiety-like and depression-like behaviors in rats under preoperative stress. Microglia were activated and pro-inflammatory cytokines, including interleukin 6 (IL-6) and tumor necrosis factor ɑ (TNF-α) were upregulated after anesthesia/surgery. The postoperative gut microbiota and metabolite composition of rats exposed to preoperative stress differed from those of control rats. Lastly, emotional impairments, metabolic alterations, and neuroinflammation returned normal in antibiotics-treated rats. Our findings provide further evidence that abnormalities in the gut microbiota contribute to postoperative metabolic restructuring, neuroinflammation, and psychiatric deficits in rats under preoperative stress.